Evasão escolar e governamentalidade : uma analítica das tecnologias de governamento para a manutenção de todos na escola - Kroetz, Ketlin (2019)
This thesis has as main objective to identify and problematize government (governance) technologies put into place to reduce school dropout rates in Basic Education. Based on the theoretical contributions of Michel Foucault, the analytical tool put into action was the notion of governmentality, a concept elaborated by the philosopher in the late 1970s. To reach the general objective of this study, the conditions of possibility for the emergence of compulsory schooling; the discourses on school dropout, as well as their effects on the risk of school dropout, are analyzed, through statistics. When choosing school dropout as an investigative subject, the research had: (I) a corpus of analysis of 75 articles extracted from three repositories; (II) ethnographic work carried in a school located in the Encosta da Serra region. From the study of the materials of analysis, it was possible to identify, in the analyzed articles, five units of analysis that operate based on a preventive order, with the purpose of mitigating the school dropout rates. These units of analysis correspond: (I) to flexibilization as a pedagogical principle; (II) to statistics as a validation tool; (III) to cooperation as an imperative to keep everyone in school; (IV) to compensation as an integration strategy; (V) to accountability as a producer of guilt. Through these technologies, a set of strategies - interest, acceleration, numerationalization, co-responsibility, participation, containment, protection, conditionality, blame - are put into action to keep students in school. In interviews with students, those who never thought about stopping studying and those who thought about stopping, but continued to study, I identified, in the first group, the production of a subject who was responsible and concerned with the social issues of the community, in addition to being a group of students seduced by the idea of joining a university. In the second group, the idea of the future and the success that education could guarantee is clear, and staying in school is seen as an exercise in overcoming oneself to achieve success. These subjects have established precepts for the conduct of their lives that takes schooling as necessary, and to remain studying is directly related to the idea that they must overcome two great enemies: themselves and the difficulties that appear on the way to achieve what they consider to be conveyed as what they call the future and stability. This contemporary form of government (governance) places responsibility on the individual for his/her emotional, economic, and personal situation, and is designed as an important element of the current government strategy - blaming and holding everyone accountable for their own destiny. In addition, it is worth considering that although these government (governance) technologies exist and work in order to prevent a certain risk, they will never be sufficient for the maintenance of everyone in the school, since they are based on an education project that is not valid for all, and because different contexts deal with school drop-out in a different way, which shows the impossibility of keeping everyone in school. Therefore, if we consider the public school as an institution that reinforces the neoliberal model, which places on the subject the responsibility for its own success and failure, it will always be possible to resist neoliberal hegemony and school drop-out can be seen, in this sense, as a way of resisting this model of schooling that is imposed: we are governed by certain mechanisms, but we resist others. If forms of governmentality, in contemporary times, use subtle mechanisms to exert power over life, in it also emerge other logics that escape the predetermined.